2022
DOI: 10.3389/fpsyg.2022.870903
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Teaching Practices During the COVID-19 Pandemic: Teachers’ Goals and Activities in Virtual Classrooms

Abstract: To research teachers’ priorities on what was to be taught and learned during the COVID-19 lockdown, we asked Spanish Primary and Secondary teachers to choose and describe the activity they preferred among those carried out with their students during the pandemic. Our interest was to investigate what really happened in the classrooms, the type of learning favored by the practices (reproductive vs. constructive), and the agreement between the teacher’s goals and their teaching We obtained 272 activities that we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 49 publications
0
4
0
8
Order By: Relevance
“…Further, due to the flaws of the educational platform, students’ interaction with the teacher, peers, and the content did not lead to the construction of a good learning atmosphere to improve students’ participation in classes ( Sun et al, 2022 ). The instruction was mostly teacher-fronted and content-centered planned, directed, and delivered by the teacher without prioritizing attitudinal goals in the designed activities ( Echeverría et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, due to the flaws of the educational platform, students’ interaction with the teacher, peers, and the content did not lead to the construction of a good learning atmosphere to improve students’ participation in classes ( Sun et al, 2022 ). The instruction was mostly teacher-fronted and content-centered planned, directed, and delivered by the teacher without prioritizing attitudinal goals in the designed activities ( Echeverría et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This fact could explain the discrepancies between the positive conceptions towards VG use and its lack of use. Several studies have shown that teachers when using digital resources manifest practices content centered ( Brun and Hinostroza, 2014 ; Mailizar and Fan, 2020 ; Pozo et al., 2021 ; Sigalés et al., 2008 ), even when they point out the opportunities of student-centered teaching ( Kaymakamoglu, 2018 ; Pérez Echeverría et al., 2022 ). This fact seems to be reflected in the lack of VG use since, by their own characteristics, are not resources that allow this centered-content teaching but require the active uses of the student from which to reflect on the events and consequences of the actions that are carried out with them.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite positive beliefs about VG of this study we think that to convert the favorable disposition of the teacher towards VG into effective practices, it is necessary to promote training with these resources. From our position, this training should be oriented not only to improve the teachers' competencies when using VG, seeking the understanding and integration of the pragmatic and epistemic elements that underlie practices with these resources, but also should be oriented to help teachers to rethink their role in teaching ( Pérez Echeverría et al., 2022 ; Pozo et al., 2021 ; Sánchez-Cruzado et al., 2021 ). In this sense, the need to promote uses with the VG that are oriented to student-centered activities is essential in today's society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estas diferentes maneras de entender el papel de las TIC en educación se relacionan con la forma de concebir los procesos de enseñanza y aprendizaje (Ananiadou y Claro, 2009;Pozo, 2020b;Pérez Echeverría et al, 2022;Ertmer et al, 2015;OECD, 2019). Desde los enfoques más tradicionales (centrados en el contenido o en el profesor), dirigidos a la enseñanza del contenido, con un énfasis en procesos asociacionistas y reproductivos, los usos educativos de las TIC suelen relacionarse con la manipulación de la información, especialmente con la facilitación de su acceso y con la comunicación y suelen ser propuestas y controladas por los profesores.…”
unclassified